Evaluasi Lingkungan Kerja (Intensitas Cahaya, Kelembaban, Suhu, dan Kebisingan) Menggunakan Metode Simple Random Sampling dan HIRADC pada PT.Vitapharm - Kadek Dina Kusuma P; Sinta Dewi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This evaluation of the working environment was carried out in order to improve health and safety at work (K3), reduce the risk of accidents at work and optimise the psychological state of the employees. The research was carried out by taking measurements in all rooms of the Quality Control Building, 1st floor and dining room. The data was analysed using Microsoft Excel software. The data was then analysed using the HIRADC method. In the noise measurements, the room with the highest noise is the Chemical Physics Laboratory Room at 81.21 dB. Then, when measuring humidity, the room with the highest humidity is the changing room at 68.90%. In the light intensity measurement, the room with the highest light intensity is the Returns Room at 1686 lux. In the temperature measurement, the room with the highest temperature is the laundry room at 33.20°C. The HIRADC analysis is then carried out to identify potential hazards that may occur and to determine improvements that can be made. Based on the HIRADC analysis, there are 7 that are in the low risk category, which has a risk level range of 1-4, marked in green. There are 9 that are in the medium risk category between 5-9 which is marked in yellow. Then there are 4 in the high risk category between 10-16, which are marked in orange. This means that the risks in the high category require in-depth action.